Вплив IoT-технологій на трансформацію бізнес-моделей стартап-підприємств у сфері цифрової охорони здоров'я - Самусь, Павло Олегович; Сергієнко, Олена Андріанівна (ТОВ "ДКС Центр", 2025)
У статті досліджено вплив технологій Інтернету речей (IoT) на трансформацію бізнес‑ моделей стартапів у сфері цифрової охорони здоров’я. Метою роботи є виявлення ключових переваг і бар’єрів впровадження IoT, а також розробка моделі участі стартапів у формуванні високотехнологічної медичної екосистеми. Використано методи контент‑аналізу наукових публікацій і кейс‑ досліджень успішних проєктів. Визначено основні переваги застосування IoT‑ рішень: безперервний моніторинг стану пацієнта, персоналізація терапії, автоматизація клінічних процесів, підвищення ефективності управління ресурсами. Окремо охарактеризовано переваги для цифрової медицини: зниження витрат, підвищення точності діагностики, розширення доступу до медпослуг та покращення комунікації з пацієнтами. Проаналізовано технічні, етичні, та кадрові та регуляторні бар’єри, що стримують впровадження IoT‑ рішень. Запропоновано структуровану модель участі стартапів через розробку SaaS‑ платформ, безпечних каналів обміну даними, адаптивних інтерфейсів та навчальних програм для медперсоналу. Наголошено на потребі інтеграції IoT із великими даними (Big Data), штучним інтелектом та хмарними сервісами для побудови стійкої медичної екосистеми й здійснення подальших міждисциплінарних досліджень у сфері стандартизації та оцінки соціально‑ економічної ефективності цифрових бізнес‑ моделей. This article examines the transformative impact of Internet of Things (IoT) technologies on the business models of startups operating within the digital healthcare sector. The study’s objective is to identify the primary advantages and challenges associated with IoT adoption and to propose a structured framework illustrating how startups can act as catalysts for innovation in the creation of integrated, high‑ tech medical ecosystems. Employing a mixed‑ methods approach that combines systematic content analysis of academic literature with case studies of leading IoT‑ enabled healthcare ventures, the research delineates four core benefits of IoT deployment: continuous patient monitoring, treatment personalization, process automation, and resource optimization. Detailed discussion highlights specific improvements in healthcare delivery, including cost reduction, enhanced diagnostic accuracy, expanded access to medical services in remote areas, and strengthened patient–provider communication. Simultaneously, the paper critically analyzes key impediments hindering widespread IoT integration—namely infrastructure deficits, data privacy and security concerns, interoperability gaps, workforce skill shortages, and ethical considerations. In response, the authors propose a comprehensive participation model for startups that leverages software‑ as‑ a‑ service (SaaS) frameworks, robust data exchange platforms, intuitive user interfaces, and tailored training programs for healthcare professionals. Emphasis is placed on the synergistic integration of IoT with cloud computing, Big Data analytics, and artificial intelligence to underpin the development of scalable, patient‑ centric ecosystems. Finally, the article underscores the necessity for further interdisciplinary research focused on standardization protocols, the establishment of public–private partnerships, and rigorous socio‑ economic evaluations of innovative digital business models in e‑ health, thereby charting a roadmap for future academic inquiry and practical implementation.
The impact of IoT technologies on the transformation of startup business models in the field of digital healthcare
Keywords: IoT у медицині; цифрова охорона здоров’я; медичні стартапи; бізнес-моделі; телемедицина; носимі пристрої; віддалений моніторинг; цифрова трансформація; IoT in healthcare; digital health; medical startups; business models; telemedicine; wearable devices; remote monitoring; digital transformation